Modeling Reactive Mixtures: Case Study for Spills of Formaldehyde Solutions. Issue 1 (2nd October 2018) - Drew, David W.; Dharmavaram, Seshu; Gilbert, Kevin L.
Abstract : When a liquid mixture, such as an aqueous formaldehyde solution, is released into the environment, the rate of evaporation into the atmosphere depends strongly on chemical reactions that regulate the evolution of formaldehyde vapors. Most of the consequence modeling methods and models currently used in the industry usually ignore any reaction phenomena. This article describes a dynamic model developed using the Aspen® Custom Modeling (ACM) tool kit. In the case of formaldehyde solutions, the thermodynamics and reaction kinetics of a mixture of formaldehyde (HCHO), water and methanol (CH3 OH) are computed from models available in the open literature. The liquid‐phase, reversible, chemical reactions between water and formaldehyde, as well as methanol and formaldehyde, form oligomers—most of which are nonvolatile. The mass transfer and heat transfer coefficients between the surface of the spill and the atmosphere are computed by established correlations for flow over a semi‐infinite flat surface. For a release scenario, the model computes the time‐varying liquid and vapor phase compositions and conditions. It also computes the required vaporization rates for HCHO and CH3 OH resulting from, for example, a 54 wt% formaldehyde solution spill onto a relatively dry surface of a fixed area under specific meteorological conditions. The article presents details regarding the formaldehyde spill modeling methodology, with examples. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 61–70, 2019